Demonstrating the Impact of Cognitive CEO on Firms’ Performance and CSR Activity - Li, Hui; Hang, Yong; Shah, Syed Ghulam Meran; Akram, Aswad; Ozturk, Ilknur (Frontiers in Psychology, 2020)
One aspect of entrepreneurship psychology also clarifies individual characteristics. Extracting from entrepreneurship psychology, cognitive CEO has been formulated using DAE statistical technique. The study elucidates that cognitive CEOs not only boosts SME performance but also invigorates corporate social responsibility (CSR) activity. The data of listed SMEs for the years 2016 -2018 is analyzed through the panel regression technique. Significantly, the study demonstrates that CEO age is positively interlinked with firms’ growth and CSR activity. Moreover, the empirical underpinning of results has also divulged that state-owned enterprises and firms with high total assets prefer cognitive CEOs, who accelerate the firms’ value and invigorate CSR activity. The number of independent directors are analyzed as a moderator and are concluded to be an intensifier for both SME growth and CSR activity. Conclusively, 2SLS instrumental panel regression signifies the veracity of empirical results.